"Si Dios Quiere": Fatalismo and use of mental health services among Latinos with a history of depression. (14th September 2017) - Rosales, Robert; Calvo, Rocío
ABSTRACT: Latinos are less likely to seek professional mental health care than other groups in the United States. While fatalismo has long been hypothesized to be responsible for this behavior, there is little evidence on this assumption. Using an adapted version of the Behavioral Model of Health Service Use (BMHSU), and a nationally representative sample, this study examined the association between fatalismo and mental health service use among Latinos with a history of depression. Participants ( n = 703) were drawn from the 2007 Pew Hispanic Healthcare survey. Results showed that fatalismo was significantly associated with the use of psychiatric care, even after controlling for traditional deterrents of health care access and utilization. The findings underscore the importance of fatalismo in predicting Latinos' use of psychiatric care. Implications for practice are discussed.